THE RELATION OF THERAPEUTIC COMMUNICATION ABILITY OF HEALTH PERSONNEL WITH THE LEVEL OF COMMUNITY KNOWLEDGE ABOUT THE DISEASE OF DENGUE HEMORRHACIG FEVER AT RT 01/RW 01 BULOK, KALIANDA LAMPUNG IN 2022 - Safitri, Rafella Desatiyanti; Agil, Hilda Meriyandah; Dinda Nur Fajri Hidayati Bunga (Soscience: Jurnal Ilmu Sosial Science, 2024)
Therapeutic communication is interpersonal communication between nurses and patients that is carried out consciously when nurses and patients influence each other and gain shared experiences that aim to overcome patient problems and improve the patient's emotional experience which will ultimately achieve healing. In the management of counseling regarding DHF, health workers apply therapeutic communication so that the level of public knowledge about DHF conveyed by health workers can be conveyed to the community optimally. This study aims to determine the relationship between the therapeutic communication skills of health workers and the level of public knowledge about DHF in RT 01/RW 01 Bulok, Kalianda, Lampung in 2022. The research method used is quantitative with cross-sectional analytical research. The population in this study were 86 people. The sample of this study was 77 respondents, data collection was done by using a questionnaire sheet. The data collection technique was using purposive sampling. The results showed that the p-value was 0.000 (value <0.05) this indicates that H0 is rejected. The conclusion of the study is that there is a relations between the therapeutic communication ability of health workers and the level of public knowledge about DHF.